The Influence of Asset and Liability Management on Dividend Policy and Firm Value of Listed Banking Companies in the Indonesia Stock Exchange - Kamaruddin; Sudirman; Nasrullah Bin Sapa; Trimulato; Supriadi; Mukhlis; Asyraf Mustamim; Safri Haliding (Pustaka Digital Indonesia, 2025)
This study examines the impact of asset and liability management on dividend policy and firm value in listed banking companies on the Indonesia Stock Exchange (IDX). The research utilizes panel data from banking statistics reports and annual IDX statistics. Structural Equation Modeling (SEM) is employed for data analysis. The findings reveal that asset management has a positive and significant effect on both dividend policy and firm value. This suggests that efficient asset allocation enhances a bank’s ability to distribute dividends and increase its overall valuation. Conversely, liability management exhibits a negative and insignificant effect on dividend policy and firm value. This indicates that an increase in liabilities does not significantly influence a company's dividend distribution or market valuation. These results highlight the importance of effective asset management in shaping financial performance and shareholder value, while liability management requires further evaluation for its role in banking stability. The study provides insights for investors, policymakers, and banking executives in optimizing financial strategies for sustainable growth and profitability.